Uso de L-asparaginase nativa de E. coli e Peg-asparaginase em crianças e adolescentes diagnosticados com leucemia linfóide aguda em um serviço público no nordeste do Brasil - Barros, Thayse Santos (2019)
Acute lymphoblastic leukemia (ALL) is the most common childhood cancer, accounting for 25% of cases of pediatric neoplasia. It originates from a clonal disorder of hematopoietic stem cells, characterized by proliferation of minimally differentiated blasts of B-cell precursor lineage (B-ALL) or, less commonly, of precursor T-cell line (T-ALL). ALL treatment is defined according to risk group stratification, adapting regimen intesification for patients with lower probability of survival. Due to this strategy survival rates for ALL are currently close to 90% in developed countries. In Brazil, L-asparaginase is a chemotherapeutic agent used to induce disease remission during an induction phase. Over the last two years the formulation of this drug to brazilian oncology centers has been constantly changing despite the different pharmacodynamic and immunogenic characteristics between the formulations. Our objective was to evaluate the influence on chemotherapy response, prognosis, toxicity, and mortality of native E. coli L-asparaginase (L-aspar) and pegylated L-asparaginase (Peg-aspar) administered during the induction phase in the treatment of children and adolescents diagnosed with ALL. For this, a prospective descriptive study was conducted with children and adolescents diagnosed with ALL from January 2017 to May 2018. The use of L-aspar or Peg-aspar was considered as an inclusion factor. 26 patients were evaluated, 14 have used L-aspar and 12 Peg-aspar. Of these, 10 (52.6%) had a negative bone marrow Minimal Residual Disease (MRD) at day 35, 4 (15.4%) relapsed and 6 (23.1%) died. In total, 4 patients (15.4%) developed hypersensitivity reaction, all using Peg-asp, what demonstrated statistical significance (p = 0.0331). No significant association was found between the use of one of the drugs and the response to chemotherapy assessed by MRD at D35 (p> 0.9999), mortality (p = 1.0000) and relapse (p = 0.1001). In conclusion, our data suggest similar prognostic results between the drugs L-aspar and Peg-aspar. However, with higher risk of hypersensitivity reaction associated with the use of Peg-aspar